The last note of warning [large type] - Schellman, Katharine (Schellman, Katharine. Nightingale mysteries., 2025)
"Prohibition is a dangerous time to be a working-class woman in New York City, but Vivian Kelly has finally found some measure of stability and freedom. By day, she's a respectable shop assistant, delivering luxurious dresses to the city's wealthy and elite. At night, she joins the madcap revelry of New York's underworld, serving illegal drinks and dancing into the morning at a secretive, back-alley speakeasy known as the Nightingale. She's found, if not love, then something like it with her bootlegger sweetheart, Leo, even if she can't quite forget the allure of the Nightingale's sultry owner, Honor Huxley. Then the husband of a wealthy client is discovered dead in his study, and Vivian was the last known person to see him alive. With the police and the press both eager to name a culprit in the high-profile case, she finds herself the primary murder suspect. She can't flee town without endangering the people she loves, but Vivian isn't the sort of girl to go down without a fight. She'll cash in every favor she has from the criminals she calls friends to prove she had no connection to the dead man. But she can't prove what isn't true. The more Vivian digs into the man's life, and as the police close in on her, the harder it is to avoid the truth: someone she knows wanted him dead. And the best way to get away with murder is to set up a girl like Vivian to take the fall"--